Pengaruh Brand Ambassador Dan Discount Price Terhadap Minat Beli Ulang Dimediasi Kepuasan Konsumen Fashion Produk Pada E-Commerce Shopee Di Semarang - Amalia Yulianti; Robertus Basiya (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The target of this study is to analyze the impact of brand ambassadors and discount prices on repurchase intention mediated by customer satisfaction with fashion products on Shopee e-commerce in Semarang. The total sample for this study was 100 respondents. In order to take samples using purposive sampling. This study uses SPSS version 26 analysis. The results of the study show that brand ambassadors have a significant & positive impact on consumer satisfaction, discount prices have a significant & positive impact on consumer satisfaction, brand ambassadors have a significant & positive impact on repurchase interest, discount prices have a significant & positive impact on repurchase interest, consumer satisfaction has a significant & positive impact on repurchase interest, consumer satisfaction mediates brand ambassador has a significant & positive impact on repurchase interest, consumer satisfaction mediates discount price has a significant & positive impact on repurchase interest. Keywords: Brand Ambassador, Discount Price, Repurchase Intention, Consumer Satisfaction